Ukrepi za izboljšanje delovnih pogojev pri platformnem delu - Strban, Grega (Delavci in delodajalci, 2025)
Platform work is a modern form of non-standard organised and paid work organised through a digital labour platform that organises, manages, and supervises the work process using automated monitoring and decision-making systems, in so-called algorithmic management. It falls within the scope of high-risk artificial intelligence (AI) systems and persons performing platform work are exposed to an increased risk of precariousness in the fields of labour and social law, as well. These are also the key challenges for regulating measures aimed at improving working conditions in platform work.
Keywords: algorithmic management; algoritmično upravljanje; artificial intelligence; decent work; digital labour platform; digitalisation; digitalizacija; digitalna platforma dela; dostojno delo; platform work; platformno delo; precariousness; prekarnost; umetna inteligenca